2011
DOI: 10.1177/2040622311430006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a protective effect of polyphenols-containing foods on cardiovascular health: an update for clinicians

Abstract: Growing evidence suggests that polyphenols could be serious candidates to explain the protective effects of plant-derived foods and beverages. Based on current studies, a general consensus has been achieved to sustain the hypothesis that the specific intake of foods and beverages containing relatively high concentrations of flavonoids may play a meaningful role in reducing cardiovascular disease (CVD) risk through an improvement in vascular function and a modulation of inflammation. This review aims at providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
157
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(162 citation statements)
references
References 150 publications
(334 reference statements)
1
157
0
4
Order By: Relevance
“…They can be divided into 6 major subclasses as a function of the type of heterocycle involved: flavonols, flavones, isoflavones, flavanones, anthocyanidins, and flavanols, while those that are comparatively minor components of the diet are dihydroflavonols, flavan-3,4-diols, chalcones, dihydrochalcones and aurones [28]. The basic flavonoid skeleton can have numerous substituents.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be divided into 6 major subclasses as a function of the type of heterocycle involved: flavonols, flavones, isoflavones, flavanones, anthocyanidins, and flavanols, while those that are comparatively minor components of the diet are dihydroflavonols, flavan-3,4-diols, chalcones, dihydrochalcones and aurones [28]. The basic flavonoid skeleton can have numerous substituents.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Chemically, flavonols differ from many other flavonoids since they have a double bond between C2-C3 and a hydroxyl group (OH) in position three of the C-ring (3-hydroxyflavones) [28]. The majority of flavonols are present as O-glycosides.…”
Section: Flavonolsmentioning
confidence: 99%
“…Although offi cial dietary intake of polyphenols and rutin has not yet been established, the total dietary intake of polyphenols was recommended to be 1 g per day (39) or about 1.2 g per day (40 % of fl avonoids, 60 % of pheno- Control=rice fl our cookies, sample 1=rice fl our cookies containing 10 % light buckwheat fl our, sample 2=rice fl our cookies containing 20 % light buckwheat fl our, sample 3=rice fl our cookies containing 30 % light buckwheat fl our Control=rice fl our cookies, sample 1=rice fl our cookies containing 10 % light buckwheat fl our, sample 2=rice fl our cookies containing 20 % light buckwheat fl our, sample 3=rice fl our cookies containing 30 % light buckwheat fl our lic acids) (40), while the intake of 10-25 mg per day of rutin for adults and 5-10 mg per day for children are considered safe (41). In this view, 100 g of cookies with 30 % light buckwheat fl our, which contain the highest amount of polyphenols and rutin among the examined cookies (Table 4), could contribute to approx.…”
Section: Total Phenolic and Rutin Contentmentioning
confidence: 99%
“…Epidemiologic studies have shown that consumption of food and beverages containing polyphenols are associated with reduced cardiovascular morbidity and mortality [1,2].…”
mentioning
confidence: 99%